Effects of the Hypoxic Radiosensitizer Misonidazole on Normal and Irradiated Epidermis - Molinari de Rey, Beatriz L.; Lanfranchi, Héctor E.; Klein-Szanto, Andrés; Itoiz, María Elina (John Wiley & Sons, Inc., 1981)
Fil: Molinari de Rey, Beatriz L. Comisión Nacional de Energía Atómica; Argentina